Combinatorial Technology as a New Method for Chemical Processes - Restu Kartiko Widi; Sharifah bee Abdul Hamid; Looi Mei Hong (Jurnal ILMU DASAR, 2009)
The ultimate goal approach to combinatorial catalysis taken in this research is from an academic perspective where the main objective is to accelerate the discovery of catalytic phenomena, i.e. new catalytic materials and catalytic processes, constrained by limited equipment and human resources. A commercially synthesis robotic workstation is used for automated parallel preparation of catalyst libraries, which is able to reproduce a conventional catalyst preparation method used routinely in laboratory, thereby increasing significantly the number of catalysts that can be prepared at once. The aim of this work is to produce libraries of catalysts based on this type of system to be tested and optimized by using the high throughput screening reactors and the selected catalysts are characterized to understand the structural properties. The 12 parallel reactors allows a proper catalyst testing, under more realistic conditions than in conventional combinatorial techniques, especially when the catalyst stage is advanced and quantitative data is required.